Balancing identities : works by architect Branko Petrović in Addis Ababa (1962-1969) = Balansiranje identiteta : radovi arhitekta Branka Petrovića u Addis Abebi (1962.-1969.) - Smode Cvitanović, Mojca (Array, 2020)
The paper deals with the facets of work by the Croatian architect and urban planner Branko Petrović in Addis Ababa, where he served as the chief architect in the Ethiopian Ministry of Public Works and Communications from 1962 to 1969. Translation of the expertise stemming from the domicile practice and adaptation to a specific construction momentum in the city are thereby being considered. The modalities of technical cooperation are simultaneously examined as a form of international knowledge exchange in the field of architecture.